2017
DOI: 10.1128/mbio.00818-17
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Exacerbates Infection via Hyperinflammation by Signaling through TLR4 and RAGE

Abstract: For more than a century, diabetic patients have been considered immunosuppressed due to defects in phagocytosis and microbial killing. We confirmed that diabetic mice were hypersusceptible to bacteremia caused by Gram-negative bacteria (GNB), dying at inocula nonlethal to nondiabetic mice. Contrary to the pervasive paradigm that diabetes impedes phagocytic function, the bacterial burden was no greater in diabetic mice despite excess mortality. However, diabetic mice did exhibit dramatically increased levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 38 publications
3
53
0
2
Order By: Relevance
“…Additionally, we observed the modulation of the LT pathway by the degree of glycemic control. MYD88 encodes an essential cytosolic adapter protein that plays a central role in signal transduction of IL1 and of TLRs [17], besides participating in AGE signaling [18]. A lower expression of MYD88 mRNA in patients with complications was an unexpected finding, especially because MYD88-dependent pathways were found to participate in the development of DR [19], and when we evaluated the expression of MYD88 mRNA in patients sorted by microvascular complications, patients with DR presented a lower expression of this gene in comparison to patients without DR, with a P value of 0.06 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we observed the modulation of the LT pathway by the degree of glycemic control. MYD88 encodes an essential cytosolic adapter protein that plays a central role in signal transduction of IL1 and of TLRs [17], besides participating in AGE signaling [18]. A lower expression of MYD88 mRNA in patients with complications was an unexpected finding, especially because MYD88-dependent pathways were found to participate in the development of DR [19], and when we evaluated the expression of MYD88 mRNA in patients sorted by microvascular complications, patients with DR presented a lower expression of this gene in comparison to patients without DR, with a P value of 0.06 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…AGE-RAGE binding activates multiple signal transduction pathways that promote atherogenesis, including increased expression of VCAM-1, macrophage inflammatory protein-1 (MIP-1), MMP9, IL-1 and TNF-α that mediate leukocyte adhesion and vascular inflammatory reactions leading to mitochondrial dysfunction and cell death [35] . RAGE ligands in addition to AGEs, including S100 calgranulin family proteins and high mobility group protein B1 can activate innate immune system responses by toll-like receptor 4 (TLR4) signaling and increased NF-κB transcription factor activity [36] . Telmisartan has anti-inflammatory activity that decreases AGE-induced C-reactive protein (CRP) generation by inhibiting RAGE expression caused by activation of peroxisome proliferator activated receptor (PPAR)-γ activation [37] .…”
Section: Hyperglycemia-induced Excessive Ros Production and Acceleratmentioning
confidence: 99%
“…Activation of TLR2 triggers the signaling pathway for myeloid differentiation factor 88 (MyD88) and further activates nuclear factor kappa-light-chain-enhancer of activated B cells (NF- κ B) in the nucleus to increase proinflammatory mediators [ 10 ]. Several studies have demonstrated that TLR4 is crucial for regulating inflammatory responses [ 11 13 ]. TLR4 is reported to recognize both exogenous pathogen-associated and endogenous damage-associated molecular patterns.…”
Section: Introductionmentioning
confidence: 99%